Intervensi Masalah Kesehatan Demam Berdarah Dengue (DBD) Melalui Program Laskar DBD di Lingkungan Cikabuyutan Barat Kelurahan Hegarsari Kecamatan Pataruman Kota Banjar Tahun 2025 - Agi Ahmad Gifari; Wulan Sundari; Sabila Syahadah Azizah; Ega Oktaviona Putri; Ilma Amaliyyah Rahmat; Santi Shopiyah; Sintia Damayanti; Sausan Karimah; Diva Nurlatifah; Shelly Putrianti Dewi; Fathiah Qolbu; Januar Nur Ismail Nugraha; Nissa Noor Annashr (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
DHF (Dengue Hemorrhagic Fever) is a disease caused by the aedes virus. WHO states that 4,000 people worldwide have died from DHF, Banjar City in 2024 had 387 cases of DHF. Based on the results of community diagnosis using the ultrasound method, it has been determined that the priority health problem is DHF (Dengue Fever). Based on the results of the SWOT analysis, it was found that the determinant factor of the health problem is non-compliance with the 3M Plus PSN which includes: empty houses are not maintained with damp and dark conditions, the community does not understand and has not implemented the 3M Plus PSN at home, and the community only recognizes DHF prevention efforts limited to fogging. Therefore, we designed innovations through the LASKAR DBD program (Collaborative Strategic Steps for Dengue Fever) with the implementation of activities in the form of revitalizing the DBD center building as a place for socialization and counseling about dengue, fishization by giving guppy fish as larvae-eating fish, held a SAMBEL (Equal Learning) program, namely the installation of 3M Plus PSN stickers in each house as educational material as well as counseling activities for cadres and school children related to DHF, then held a BALADO program (Together Fighting Dengue with ovitrap) which is a modified SAMT ovitrap demonstration activity.